Large-scale computer-mediated training for management teachers - Gilly Salmon; Ken Giles; John Allen (Information Research: An International Electronic Journal)
In 1995/6 the Open University Business School (OUBS) trained 187 tutors in the UK and Continental Western Europe in Computer Mediated Conferencing (CMC) for management education. The medium chosen for the training was FirstClassTM. In 1996/7 the OUBS trained a further 106 tutors in FirstClassTM using an improved version of the previous years training. The on line training was based on a previously developed model of learning on line. The model was tested both by means of the structure of the training programme and the improvements made. The training programme was evaluated and revised for the second cohort. Comparison was made between the two training programmes.